2015
DOI: 10.1007/978-981-287-760-4_1
|View full text |Cite
|
Sign up to set email alerts
|

Plasma-based Radar Cross Section Reduction

Abstract: The concealment of aircraft from radar sources or stealth is achieved either through shaping, or radar absorbing coatings, or engineered materials, or plasma, etc. Plasma-based stealth is a radar cross-section (RCS) reduction technique associated with the reflection and absorption of incident electromagnetic (EM) wave by the plasma layer surrounding the structure. Plasma cloud covering the aircraft may give rise to other signatures such as thermal, acoustic, infrared, or visual. Thus it is a matter of concern … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…Plasma RCS reduction is an attractive technique associated with the scattering and absorption of the incident wave by the plasma layer surrounding the structure [6]. Plasmas as a dispersive and active electromagnetic ambient are being raised in the plasmawave interaction.…”
Section: Introductionmentioning
confidence: 99%
“…Plasma RCS reduction is an attractive technique associated with the scattering and absorption of the incident wave by the plasma layer surrounding the structure [6]. Plasmas as a dispersive and active electromagnetic ambient are being raised in the plasmawave interaction.…”
Section: Introductionmentioning
confidence: 99%
“…An atmospheric pressure plasma is considered and it is assumed cold, collisional, and inhomogeneous. In a cold plasma, the effects of the electron temperature on the electron number density and electron‐neutral collision frequency are negligible [1]. For a lossy environment and locations far away from the source, the Maxwell curl equations are as follows:×H=σE+Dt, ×E=Bt, where E is the intensity of the electric field and D is the electric flux density.…”
Section: Model Descriptionmentioning
confidence: 99%
“…In contrast, plasma as a non‐solid absorbent does not have the mentioned constraints and allows strong absorption with significant frequency bandwidth. Also, it has been reported that plasma‐based absorption is applicable in airplanes and satellites [1]. In addition to wave absorption, inhomogeneous plasma coating improves further attenuation of the backscattered wave, through wave bending from the high‐density regions to low density.…”
Section: Introductionmentioning
confidence: 99%
“…The scattering of waves by canonical structures buried in a plasma medium is a very interesting problem as plasma‐based stealth is directly related with the reduction technique of radar cross section (RCS). [ 1 ] A multilayer stealth structure composed of uniform plasma and radar‐absorbing material (RAM) was presented in a study focussed on overcoming some drawbacks of stealth technology. [ 2 ] Besides, the radiation characteristics of a satellite antenna tuned by a plasma load were investigated both theoretically and experimentally in a study.…”
Section: Introductionmentioning
confidence: 99%